ARTIFICIAL INTELLIGENCE IN LANGUAGE EDUCATION: OPPORTUNITIES AND CHALLENGES - Mohlaroyim Nematova; Gulsevar Usmonova (Bright Mind Publishing, 2025)
Artificial Intelligence (AI) can facilitate and enhance various aspects of human existence, such as transportation, healthcare, entertainment, and education. In recent years, AI-powered language learning tools have gained significant attention due to their potential to revolutionize language teaching and learning. This article talks about artificial intelligence in language teaching: opportunities and challenges.
Keywords: Artificial intelligence, English language teaching, tools, benefits, challenges, education, transportation, healthcare, entertainment, attention.